Mineral development for growth: the case for a new mineral policy framework for Pakistan. Issue 3 (2nd October 2017) - Ashraf, Hamid; Cawood, Frederick
Abstract : Purpose: The fundamental purpose of this research is to compare Pakistan's mineral policy instrument with that of leading developing minerals-based economies and to highlight the gaps. Mineral resources development can act as an engine for country growth and have the potential to transform economies and societies. The extent to which such transformation takes place varies depending upon the method of their use. Design/methodology/approach: This paper conducts a gap analysis between Pakistan and leading developing minerals-based economies to identify key policy gaps. Two basic principles were kept in mind with the choice of countries: first, only developing countries were considered and, second, at least two countries had to be Islamic. Eight developing countries Chile, Mexico, Brazil, Peru, India, South Africa, Kazakhstan and Turkey were selected. Findings: The most important finding of the exercise is that Pakistan's mineral sector is lacking an enabling institutional, fiscal and regulatory framework for the optimal development of its mineral resources. Practical implication: Pakistan's mineral resources have the potential to expand its economy and benefit its citizens. For this to happen, Pakistan must first establish what beneficiation is realistically expected from its mineral resources and, second, formulate a mineral policy based on leading practices to attract mining investment and aim for a sector contribution to gross domestic product of 5 per cent. Originality/value: This paper presents original work on how Pakistan should formulate its mineral policy to extract maximum benefit from its mineral resources.